A DIGITAL INVESTIGATION OF DISHES AND HOUSEHOLD UTENSIL LEXICON IN ENGLISH AND ITS REGIONAL DIALECTS - Jo’rayeva Shaxinabonu Farmon qizi; Abduvahobova Mahina Azatovna (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article examines the lexical variation of dishes and household utensils in English across different regional dialects, focusing on British English, American English, Scottish English, and Australian English. Dishes and household items play a central role in everyday communication, and their names often carry cross-cultural significance. The research is conducted within the frameworks of lexicology, cognitive semantics, dialectology, stylistics, and theoretical grammar. Through corpus-based analysis, etymological investigation, and comparative dialectal mapping, the study demonstrates that this lexical field is culturally significant, semantically productive, and deeply involved in metaphorical and idiomatic usage. The findings contribute to the advancement of knowledge in lexicology and dialectology by providing a detailed examination of everyday vocabulary as a reflection of cultural identity and linguistic diversity.